Development of a Gamification-Based Tajweed E-Module to Improve the Qur’an Reading Skills of Madrasah Diniyah Students - Sefilla Ghilda Ikhsani; Djono Djono; Mohammad Muchtarom (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2026)
Many Madrasah Diniyah students still experience difficulties in understanding and applying Tajweed rules due to the limited use of interactive and technology-based learning media. In addition, conventional teaching methods often reduce students’ motivation and engagement during the learning process. This study aims to develop a Gamification-Based Tajweed E-Module and examine its feasibility, practicality, and effectiveness in improving the Qur’an reading skills of Madrasah Diniyah students. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through media and material expert validation, teacher practicality tests, and limited student trials. The results of expert validation indicated that the e-module is highly feasible, with an average score of 3.78 (95%) from media experts and 3.84 (96%) from material experts. Teacher practicality tests showed an average practicality percentage of 95%, while student responses averaged 92%. These findings suggest that the e-module is user-friendly, engaging, and can enhance students’ learning motivation. The application of gamification elements, such as points, levels, interactive quizzes, and audio-based learning, was proven to increase student engagement during learning activities. Therefore, the Gamification-Based Tajweed E-Module can be considered an effective, practical, and enjoyable learning medium for improving the Qur’an reading skills of Madrasah Diniyah students.